Keunggulan ekspor antar negara dan daya saing produk UMKM Indonesia dengan Pendekatan Gravity Model - Alvis Rozani; Nurul Huda (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2022)
This research analyzes the potential export development of Indonesian SME products in 12 main export destination countries and determines the ranking of export destination countries. The study used a model of gravity that is distance as an indirect variable. The study results found that the average value of the development of the relative export potential of Indonesian SME products is the most in-demand are agricultural raw material products such as palm oil, coffee, and forest products. Other potential such as textile products is also a potential market share is high in the export destination country. Based on the ranking of export destination countries, the United States ranks first with a holding capacity value (Di = AiHi) of 42,895,457.11, then Japan at 10,890,740.61, then Germany with a value of 5,488,387.57. In general, export destinations in these countries are dominated by plantation products and textile products of textile products. Thus it can be concluded that Indonesian SME export products have competitiveness in 12 export destination countries.